Differences Mastery Of Geography Concept Of Students Who Are Teached With Phet-Based Computer-Based Models And Students Are Teached Conventional On Basic Material Know The Earth (Experimental Study At Man I Kendari - Alam, Muhammad; Nursalam, La Ode; Amaluddin, La Ode (UNM Geographic Journal, 2017)
This research aim to know differences mastery of geography concept of students who are teached with phet-based computer-based models and students are teached conventional on basic material know the earth at MAN I Kendari. The population of this study is All students class X MAN 1 Kendari enrolled in the 2015/2016 school year consisting of 3 classes with the number 86. The sample of this study is class X IPS2 and X IPS3 selected by using Barlet test that the results of all classes are homogeneous to the level Î‘ = 0.05, indicated by the value of Ï‡2 hit = 274.59 <Ï‡2 = 5.99 Analysis of data in this study through descriptive and inferential analysis From the analysis of descriptive pre-test the experimental class obtained the maximum value of 53.3 and the minimum value of 13.3, the average value 32.82 and standard deviation of 10.27, while the control class pre-test obtained a maximum value of 50 and a minimum value of 6.6, the average value 29.11 and deviation standard 10.57. Post-test experimental class obtained maximum value 93.3, minimum value 30.6, average value 70.23 and standard deviation 15.19; While the control class post-test obtained a maximum value of 90, a minimum value of 25; Average value of 61.42 and standard deviation of 15.43. From inferential statistical results to test the hypothesis shows that hypothesis I, obtained the value -t (1-Î± / 2) / dk <thit <t (1-Î±) t (-0.975) (54) -1.331 <2.00, (interpolation) With Î± = 0.05 this shows no significant difference between the mean pre-test of the experimental class and the control class pre-test. In the second hypothesis, the value of t (0.975) (54) 1.673 (2.153> 1.673) indicates that the average post-test grade of the experimental class is better than the average post-test value of the control class. Hypothesis III, obtained the value of thit> t (0.975) (54) 1.673 (1.673 <1.792) which means that there is a significant difference between the gain value of the experimental class and the control class gain. This means that computer-assisted learning is more effective than conventional learning in an effort to improve the mastery of student learning concepts of class X on the subject of knowing the earth with 95% confidence level (Î± = 0.05).